Baitul Mal strategy in increasing community interest in paying zakat, infaq and shadaqah in Baitul Mal Aceh Tamiang - sari, juli dwina; Muhammad Uzair Zulkifly; Meylianda (ASNAF : Journal of Economic Welfare, Philantrophy, Zakat and Waqf, 2022)
Objectives – to find out the Baitul Mal strategy in increasing public interest in paying zakat, infaq and alms at Baitu Mal Aceh Tamiang. Methods – The research method used is descriptive qualitative with interview as the instrument Findings – The results of this study explain that by increasing the socialization program implemented by Baitul Mal, will yield on the public awareness and knowledge on the programs. Promotions which are undergone will be in the forms of billboards, banners and institutional website in order to make it easier for the public in gaining information related to Baitul Mal and its program. Practical Implication – The results of this study can be utilised as a reference by the government, especially zakat institutions